Kajian Literatur: Dampak Penerapan HACCP dan Sistem Mutu dalam Peningkatan Daya Saing pada Industri Pengolahan Ayam - Khotimatul Barki (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2023)
Trade competition in the era of globalization is getting tougher, but food processing businesses from both agricultural and animal raw materials still have a good chance to survive. Products that have good quality and food safety can compete in domestic and international markets. To maintain food safety, business owners can implement quality assurance systems such as HACCP (Hazard Analysis Critical Control Point). HACCP needs to be implemented to further improve competitiveness and be able to run a business sustainably. The method used in this research is a systematic literature review. The result of this study is the application of HACCP is expected to improve quality and be able to increase sustainable competitiveness. Most of the chicken processing industry has implemented HACCP by the elements in the appropriate HACCP program. The application of HACCP ensures the quality of food quality and avoids health hazards in the final product. The implementation of HACCP requires continuous training and education on HACCP to ensure a more stable system is implemented and the need for the use of complete personal protective equipment (PPE) to maintain hygiene during the production process.